The Use of Baamboozle to Improve Vocabulary Mastery of High School Students - Rahma Hidayatul Tafiana; Th. Cicik Sophia Budiman; Ajeng Setyorini (Journal of English Language Learning, 2025)
This study investigates the use of Baamboozle as a digital learning tool to enhance vocabulary mastery among 10th-grade students at SMA Negeri 1 Mranggen. The research employs a pre-experimental design involving a pre-test and post-test to assess students’ vocabulary mastery before and after the intervention. The findings reveal that students initially demonstrated low vocabulary mastery, with many categorized as “poor” or “very poor.” Following a two-week intervention utilizing Baamboozle, results indicate a significant improvement in students’ vocabulary scores, with a notable increase in the number of students achieving “good” and “excellent” classifications. Statistical analysis confirms a significant difference between pre-test and post-test scores, highlighting the positive impact of interactive and gamified learning on vocabulary acquisition. The study underscores the importance of engaging teaching methods to foster student motivation and enhance learning outcomes in language education.